(untitled) (Editora Impacto Científico, 2025)
Artisanal fishing in São Francisco de Itabapoana, in the interior of the state of Rio de Janeiro, is marked by the prominence of men’s work. The men who work on the high seas are mainly responsible for fishing. However, women are delegated the tasks of the processing stages, which are devalued and seen as an aid to men’s work. This analysis is based on a bibliographical review of important literature on the subject, and on the data collected by the PEA Pescarte census in 2016. When asked if there is men’s work and women’s work in fishing, 46% of respondents answered yes, indicating that almost half of the participants see distinctions in the roles played by each gender. It should also be noted that 89% of respondents said that fishing is man’s activity, showing that there is too much of a gender stereotype that associates fishing with a masculine activity. Another noteworthy point is that 5.2% of those interviewed said that fishing is an activity for women. These results elucidate the invisibility of women in fishing, the difficulty in gaining rights and recognition as fisherwomen. It is therefore necessary to raise debates with artisanal fishing communities about the importance of women’s work and demands to the public authorities for equal access to rights.